Computational mechanics software as a service project - García Garino, Carlos (2013)
Cloud computing promises great opportunities for the execution of scienti c and engineering applications. However, the execution of such kind of applications over Cloud infrastructures requires the accomplishment of many complex processes. In this paper we present a Computational Mechanics Software as a Service (SaaS) project which will allow scientists to easily con gure and submit their experiments to be transparently executed on the Cloud. For this purpose, a nite element software called SOGDE is used to perform parametric studies of computational mechanics on the basis of underlying computing resources. Moreover, a web service provides an interface for the abovementioned functionalities allowing the remote execution of scienti c applications in a simple way.